A Study On Employed Job Seekers' Acceptance Of Social Networking Sites As A Job Search Tool - Michelle, Kow Pei Ming (2009)
The use of social networking sites to connect with friends, relatives and business contacts have been the latest trend. People from all ages, various backgrounds, different ethnicity and etc. are using Social networking sites to connect with one another. The social networking sites such as Facebook, Friendster and MySpace are widely used by users to connect with friends and relatives as well as new friends, whereas Linkedln is a business oriented social networking sites where users connect with business contacts in hope of gaining new career opportunities or new business ventures and etc. With the recent economic meltdown and the need to reduce costs, companies are looking into alternative ways to source for potential candidates. Companies have been using social networking sites to connect with the potential passive candidates as well as provide the avenue for employed job seekers to connect with the recruiters of the company and be updated on the latest job openings. This research studied on the factors that influence employed job seekers acceptance of social networking sites as a job search tool.